Ammonia Synthesis: Photocatalytic Nitrogen Reduction by Ti3C2 MXene Derived Oxygen Vacancy‐Rich C/TiO2 (Adv. Sustainable Syst. 4/2021). (14th April 2021) - Qian, Jing; Zhao, Sen; Dang, Wenqiang; Liao, Yuan; Zhang, Wen; Wang, Hui; Lv, Lingling; Luo, Lei; Jiang, Hai‐Ying; Tang, Junwang
Abstract : In article number 2000282, Hai‐Ying Jiang, Junwang Tang and co‐workers fabricate a novel TiO2 architecture with abundant vacancies in a repeatable manner, by using Ti3 C2 MXene as a precursor. The fabricated novel TiO2 architecture is demonstrated to be highly effective for the photocatalytic NH3 synthesis process, which is a sustainable approach in the context of the nitrogen circle.